Measuring the Welfare Effects of Shame and Pride - Butera, Luigi; Metcalfe, Robert; Morrison, William; Taubinsky, Dmitry (American Economic Review, 2022)
Public recognition is frequently used to motivate desirable behavior, yet its welfare effects—such as costs of shame or gains from pride— are rarely measured. We develop a portable empirical methodology for measuring and monetizing social image utility, and we deploy it in experiments on exercise and charitable behavior. In all experiments, public recognition motivates desirable behavior but creates highly unequal image payoffs. High-performing individuals enjoy significant utility gains, while low-performing individuals incur significant utility losses. We estimate structural models of social signaling, and we use the models to explore the social efficiency of public recognition policies. (JEL C93, D64, D82, D91)